Discourses of Professionalism in Family Day Care. (June 2013) - Cook, Kay; Davis, Elise; Williamson, Lara; Harrison, Linda J.; Sims, Margaret
Family day care in Australia is currently undergoing rapid 'professionalisation' within a national reform agenda that seeks to raise and standardise early childhood service quality. Included within this reform is a requirement that all family day care workers obtain formal qualifications and that workers are referred to as 'educators' rather than 'carers'. This study drew on focus groups and interviews with family day care workers, management, government and industry representatives collected as part of a larger study into family day care workers' capacity to promote children's social and emotional wellbeing. Our analysis identified three discourses of professionalisation within family day care that provide important insights into the sector at a time of significant change. Management promoted workers as 'educators' aligned with a neo-liberal, masculine understanding of professionalism and the objective measures used to assess service quality. This discourse excluded what 'carers' felt were important, subjective and maternal aspects of their service delivery. To reconcile these discursive extremes, some workers took up a discourse that emphasised the requirements of their 'job' and the standards of professionalism required by management. In conclusion, we contend that the take-up of educational discourses in family day care produce and reproduce tensions between 'women's work' and 'masculine professionalism' that undermine the sector's attempts to increase their status and recognition.